2022
DOI: 10.1155/2022/6821810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depressurizing Boreholes on Energy Dissipation in Deep Roadway

Abstract: Depressurizing borehole drilling is an effective approach to control the large deformation of deep roadway. It can transfer the high stress in the proximity of the roadway into the deep stable rock masses. However, it should be noted that the borehole drilling will inevitably cause the secondary damage to roadway. To determine the parameters of depressurizing boreholes, the degree of the secondary damage must be evaluated properly. Given that the rock mass failure is an unstable phenomenon driven by energy, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Xie et al [26,27] analyzed the deformation and failure process of rock from the perspective of energy through a series of studies, revealed the energy dissipation and energy release characteristics of this process, and discussed the internal relationship between energy dissipation and energy release in the deformation and failure process of rock and rock strength and overall failure. Wang et al [28] analyzed the influence of borehole pressure relief on roadway energy dissipation by means of numerical simulation, laboratory test and theoretical analysis. Yi et al [29] studied the transfer and dissipation of strain energy in deep roadway surrounding rock under strain softening and dilatancy, and obtained some beneficial results.…”
Section: Plos Onementioning
confidence: 99%
“…Xie et al [26,27] analyzed the deformation and failure process of rock from the perspective of energy through a series of studies, revealed the energy dissipation and energy release characteristics of this process, and discussed the internal relationship between energy dissipation and energy release in the deformation and failure process of rock and rock strength and overall failure. Wang et al [28] analyzed the influence of borehole pressure relief on roadway energy dissipation by means of numerical simulation, laboratory test and theoretical analysis. Yi et al [29] studied the transfer and dissipation of strain energy in deep roadway surrounding rock under strain softening and dilatancy, and obtained some beneficial results.…”
Section: Plos Onementioning
confidence: 99%